2012
DOI: 10.5455/vetworld.2012.197-200
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of natural exposure of camels Camelus dromedaries to foot and mouth disease virus

Abstract: The World Organization for Animal Health (OIE) Code chapter on FMD includes camelids as being susceptible species to FMD similar to cattle, sheep, goats and pigs. A total of 376 field camel sera, collected from different regions of Riyadh and AlQassim Province in the Kingdom of Saudi Arabia, were screened for the presence of antibodies produced against 3ABC non-® structural proteins (NSP) of FMDV using a commercially available kit , PrioCHECK FMDV NS. Sera that tested positive on NSP were screened for serotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…The Camelidae are found in countries like North and East Africa, Middle and East Asia as well as South America where FMD is endemic (Du et al, 2009 (Yousef et al, 2012). The two closely related camel species of Bactrian and dromedary camels possess noticeably different susceptibility to FMD virus (Larska et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The Camelidae are found in countries like North and East Africa, Middle and East Asia as well as South America where FMD is endemic (Du et al, 2009 (Yousef et al, 2012). The two closely related camel species of Bactrian and dromedary camels possess noticeably different susceptibility to FMD virus (Larska et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Bactrian camels under experimental studies can easily develop obvious clinical sign of FMD (Larska et al, 2009), while several investigation appear to suggest that dromedaries are less susceptible to inoculation with FMD virus serotype O but that they do not present a risk in transmitting the disease to susceptible animals (Wernery and Kaaden, 2004;Alexandersen et al, 2008). However, Kumar et al (1983) have described the isolation of FMDV serotype O from one of two randomly selected dromedaries in India, and Moussa et al (1987) in Egypt described a strain of type O FMD virus isolated in Giza from a camel with vesicular, ulcerative stomatitis and they suggested that dromedaries are susceptible to natural FMD infection (Yousef et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations